Cleaner production and energy conservation for sustainable development - Staniškis, Jurgis Kazimieras; Jayaraman, C. (Centre for Science & Technology of the Non-Aligned and Other Developing Countries, 2010)
Papers presented at an international workshop on "Cleaner Production and Energy Conservation for Sustainability", held at Kochi during 24-26 June 2008 organized by Centre for Science & Technology of the Non-Aligned and Other Developing Countries jointly with the Society of Energy Engineers and Managers